Inhibitions of monoamine oxidases and acetylcholinesterase by 1-methyl, 5-phenyl substituted thiosemicarbazones: Synthesis, biochemical, and computational investigations. (December 2020) - Mathew, Githa Elizabeth; Oh, Jong Min; Mohan, Kumar; Kumudhavalli, M.V.; Jayanthi, Sivaraman; Kim, Hoon; Mathew, Bijo
Graphical abstract: Highlights: Eleven methylthiosemicarbazones were prepared and characterised. Inhibitory activities against monoamine oxidase (MAO) and acetylcholinesterase were evaluated. Compound MT5 was non-toxic, and reversible competitive inhibitor for MAO-B (IC50  = 8.77 μM). MT5 binding was stabilized by hydrogen bonding to Cys172 and π–π hydrophobic interaction with Tyr326 of MAO-B. MT5 may be considered a potential compound for the treatment of neurodegenerative disorders. Abstract: A series of eleven 1-methyl, 5-phenyl substituted thiosemicarbazones (MT1–MT11 ) with the phenyl ring substitutions were prepared and investigated for their inhibitory activities against monoamine oxidases (MAOs) and acetylcholinesterase (AChE). [4-(dimethylamino) phenyl]methylidene}- N -methylhydrazine-1-carbothioamide (MT5) inhibited MAO-B potently with an IC50 of 8.77 μM. Potencies for MAO-B increased in the order N(CH3 )2 in MT5  > OCH3 in MT3  > Br in MT9 . Most of the 11 compounds weakly inhibited AChE by <30% at 10 μM. MT5 competitively inhibited MAO-B and Ki value was 6.58 ± 0.064 μM. Reversibility experiments showed MT5 also reversibly inhibited MAO-B. MTT assays revealed that MT5 and MT3 were non-toxic to normal VERO cell lines with IC50 values of 191.96 and 187.04 μg/mL, respectively. From the molecular docking, MT5 binding was found to be stabilized by hydrogen bonding to the non-bonding electron of the terminal N-methyl group with Cys172 (binding energy = −7.01 kcal/mol) of MAO-B. The molecular dynamics further predicted that MT5 had a major π–π hydrophobic interaction with Tyr326 of MAO-B, suggesting that it plays an important role in the stabilization of protein-ligand interaction.These results documents that MT5 is a moderately selective, reversible, and competitive inhibitor of MAO-B with low cytotoxic profile.